RETRACTED (ditarik) : BCS : Blockchain Smart Curriculum System for Verification Student Accreditation - Dede Cahyadi; Adam Faturahman; Hendriyanti Haryani; Ellen Dolan; Shofiyul millah (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2021)
The main objective of Higher Education is to prepare students who have academic abilities in developing knowledge and intellectual development of students to prepare technology to enter the world of work. The linkage of higher education and employment is the reason why the services provided by educational institutions direct opportunities for students to find work, because the current job market places more emphasis on the educated workforce. Therefore, tertiary institutions must have a good curriculum structure, requiring students to be productive, creative and innovative individuals who aim to form character students with the level of expertise required by the world of work. This study presents a work funded by the European Union, namely the Qualichain research project which aims to test the quality of education with the labor market related to Blockchain technology. The aim of this research is to develop a Qualichain platform that will offer educational qualifications that focus on the potential of Blockchain technology and perform data analysis to support the curriculum optimization process. This Quanlichain platform will prove its implementation that there are four pilot cases that have their respective differences. Therefore the research is focused on optimizing the administration of higher education through data developed with algorithmic and semantic techniques to support decision making that will be applied in tertiary institutions.